Forecasting Optimalization in Spare Part Inventory Applications on XYZ Temanggung Outlet Ltd. - Anwar, Tulkhah Mubasyir; Yudatama, Uky; Primadewi, Ardhin (Universitas Muhammadiyah Yogyakarta, 2024)
XYZ Magelang Branch Ltd is a company engaged in the automotive sector, which supported by three outlets. The name of the outlet are Temanggung Outlet, Purworejo Outlet, and Kebumen Outlet. The Temanggung Outlet is one of the outlet with the highest number of services compared to the others. The impact of having the highest number of services is that the demand for spare parts is also the highest compared to the other outlets. To overcome the demand for spare parts at the Temanggung Outlet, an inventory application is needed to manage spare parts with the implementation of forecasting to determine the stock of spare parts for the upcoming period. In this research, the forecasting calculation is carried out by utilizing the historical calculation of the outgoing transaction data in the inventory application. The data obtained from the sales transaction report is in the form of spare parts sales with a data quantity of 30 items, selected from the top 30 spare parts sales. The calculation process using the Single Moving Average (SMA) forecasting is validated using Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE). In this research manuscript, SMA has MAPE error with range 0% up to 62.069% compared to the conventional method, which has range 16% up to 83%.